Melanotic neuroectodermal tumor of infancy: A rare pediatric head and neck lesion. Issue 6 (4th September 2018) - Owen, Bryce; Foster, Kimberly; Carlson, Andrew; Santa Cruz, Karen; Smidt, Aimee
Abstract: Melanotic neuroectodermal tumors of infancy are rare tumors arising from the neural crest and typically present during the first 12 months of life. The majority involve the facial bones, although melanotic neuroectodermal tumors of infancy of the skull and extremities have been observed with less frequency, as in the present case. This entity may initially be presented to the dermatologist as a scalp mass and should be considered in the differential diagnosis of infants with rapidly growing head and neck lesions.